APLIKASI METODE SELF-POTENTIAL UNTUK PEMETAAN BAWAH PERMUKAAN DI AREA KAMPUS ITK - Arisalwadi, Meidi; Cahyani, Rori Shanaz; Septiana, Atut Reni; Rahmania, Rahmania; Sastrawan, Febrian Dedi (Indonesian Physical Review, 2020)
Identified subsurface composition remains one of the important things in development, such as finds out potential that is below the surface, this research in Institut Teknologi Kalimantan Campus (ITK). This study aims to identify distribute potential values and finds out the source of anomalies in the ITK Campus area. This study uses the Self-Potential method with a fixed-base technique. The data obtained in the form of potential difference (delta V) data, base potential data and measurement point coordinates. The data was corrected by daily base variation, daily correction and reference correction. After obtaining a potential value from the correction at each measurement point, the data processing was done using surfer 11 software. The results of data processing were obtained isopotential contour map and qualitative interpretation which could be seen distribution of potential different values. On the isopotential contour map, slicing of two cross sections selected indicates the source of anomaly. Anomalous potential values of 45 mV to -55 mV indicated anomalous sources namely electrolyte potential in groundwater with positive anomaly values negative up to hundreds of mV. And, there was a potential for a liquid flowwith a positive and negative anomaly â‰¤ 100 mV